Biopolymer- and Natural Fiber-Based Biomimetic Tissues to Realize Smart Cosmeceuticals and Nutraceuticals Using an Innovative Approach - Pierfrancesco Morganti; Maria-Beatrice Coltelli; Alessandro Gagliardini; Andrea Lazzeri; Gianluca Morganti; Giovanna Simonetti; Tilman Fritsch; Vittorio Calabrese; Alessandra Fusco; Giovanna Donnarumma (MDPI AG, 2023)
More sustainable and smart cosmeceuticals and nutraceuticals are necessary due to the ecological transition. In this study, a pullulan-based water solution containing chitin nanofibril-nano-lignin (CN-LG) complexes that encapsulate fish collagen polypeptide, allantoin and nicotinamide was electrospun onto a nonwoven substrate made of bamboo fibers to obtain a smart nanostructured bilayer system for releasing active molecules onto the skin or other body tissues. Infrared spectroscopy was used to characterize the composition of the bilayer system before and after rapid washing of the sample with distilled water and liquids mimicking physiological fluids. The viability of keratinocytes was studied as well as the antioxidant activity, protective activity towards UV light, metalloproteinase release of aged fibroblasts and the inhibitor activity against collagen degradation. Immunomodulatory tests were performed to investigate the anti-inflammatory activity of the bilayer system as well as its indirect antimicrobial activity. The results indicate that the bilayer system can be used in the production of innovative sustainable cosmeceuticals. In general, the adopted strategy can be extended to several smart treatments for fast release that can be commercialized as solid products, thus avoiding the use of preservatives and water.